Economic policy uncertainty, credit risks and banks' lending decisions: Evidence from Chinese commercial banks - Qinwei Chi; Wenjing Li (China Journal of Accounting Research, 2017)
Using data for Chinese commercial banks from 2000 to 2014, this paper examines the effects of economic policy uncertainty (EPU) on banks' credit risks and lending decisions. The results reveal significantly positive connections among EPU and non-performing loan ratios, loan concentrations and the normal loan migration rate. This indicates that EPU increases banks' credit risks and negatively influences loan size, especially for joint-equity banks. Given the increasing credit risks generated by EPU, banks can improve operational performance by reducing loan sizes. Further research indicates that the effects of EPU on banks' credit risks and lending decisions are moderated by the marketization level, with financial depth moderating the effect on banks' credit risks and strengthening it on lending decisions.
Keywords: G21; O17; D21; 650; Economic policy uncertainty; Credit risks; Lending decisions